(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
A finite element is developed to discretize spatially one-dimensional transient heat conduction problems in both space and time. Stability of the recursive discretized equation is proved using the eigenvalues of the amplification matrix. Convergence, in this case, stems naturally from the formulation consistency of the developed finite element. Numerical experiments demonstrate that refined models are in close agreement with the exact solution.